Forecasting the Burden of Advanced Knee Osteoarthritis over a 10-Year Period in a Cohort of 60–64 year-old US Adults - Holt, Holly L. (2010)
OBJECTIVE: To forecast the burden of symptomatic knee osteoarthritis (OA) in the elderly US population over a 10-year horizon. DESIGN: Using a computer simulation model of the natural history and management of knee OA combined with population-based data from the 2008 US Census we projected the 10-year burden of knee OA among persons 60–64 years of age. Knee OA incidence and progression rates were derived from national cohorts and calibrated to published literature. RESULTS: Using national data we estimated that 13% of 14,338,292 adults 60–64 years old have prevalent symptomatic, radiographic knee OA. Among persons surviving the next decade, 20% will have symptomatic advanced (Kellgren-Lawrence [K-L] grade 3) or end-stage (K-L 4) knee OA. Prevalence of advanced knee OA will range from 10% among non-obese to 35% among obese persons. Our estimates show that a more sensitive imaging tool, such as magnetic resonance imaging (MRI), may increase the number OA cases diagnosed by up to 94% assuming that 50% of all ‘pre-radiographic knee OA’ (K-L 1) has some evidence of cartilage degeneration seen on MRI. CONCLUSIONS: Projecting new and advanced cases of knee OA among persons aged 60–64 years over the next decade creates a benchmark that can be used to evaluate population-based benefits of future disease-modifying OA drugs that are currently undergoing testing at various stages.